Emamectin benzoate in tilapia: Alternative method for drug incorporation into feed and associated residual depletion study - Neto, Pedro Fraccarolli; da Silva, Agnaldo Fernando Baldo; Moro, Evandro Bilha [UNESP]; Pilarski, Fabiana [UNESP]; de Freitas, Osvaldo; Mooney, Mark H.; Paschoal, Jonas Augusto Rizzato (Elsevier, 2019)
Due to the lack of regulated drugs for aquaculture, the present study considered specific issues relating to environmental and food safety aspects concerning the potential use of emamectin benzoate (EMA) in freshwater fishes such as tilapia (Oreochromis niloticus) – an important commercial fish species worldwide. The residual depletion of EMA (EMA-B 1a ) in fillet (muscle plus skin in natural proportions) of tilapia treated with a daily dose of 50 μg/kg BW during seven consecutive days was evaluated. To facilitate this, analytical methods for quantitation of EMA in fish feed and in fish fillet employing LC-MS/MS were developed and validated. To eliminate the risk of EMA leaching from feed into the aquatic environment during fish medication via oral administration, a promising procedure for drug incorporation into feed involving the coating of feed pellets with ethyl cellulose polymer containing EMA was evaluated. The medicated feed exhibited good homogeneity (CV < 2.1%) with negligible EMA release (< LOQ) when the medicated feed remained in the water for up to 20 min. Depletion study analysis revealed the highest EMA concentration obtained in fish fillet to be 13.3 ng/g. Therefore, under the employed rearing conditions of this study, the obtained results did not evidence requirement for a minimum withdrawal period to be proposed considering the maximum residue limit of 100 μg/g for fish muscle. In response to the well-recognized demands and need for new alternative veterinary drugs for use within aquaculture, this study offers impetus for consideration of EMA use in tilapia taking into account environmental contamination and food safety issues.
Keywords: Aquaculture; Emamectin benzoate; Food safety; Residual depletion; Tilapia; Veterinary drug residues; Withdrawal period